Cell loaded hydrogel containing Ag‐doped bioactive glass-ceramic nanoparticles as skin substitute: Antibacterial properties, immune response, and scarless cutaneous wound regeneration - Esmaeel Sharifi; Seyede Athar Sadati; Satar Yousefiasl; Rossella Sartorius; Mahdi Zafari; Leila Rezakhani; Morteza Alizadeh; Ehsan Nazarzadeh Zare; Shadi Omidghaemi; Fatemeh Ghanavatinejad; Mohammad‐Saeid Jami; Erfan Salahinejad; et al. (Wiley, 2022)
Abstract An ideal tissue‐engineered dermal substitute should possess angiogenesis potential to promote wound healing, antibacterial activity to relieve the bacterial burden on skin, as well as sufficient porosity for air and moisture exchange. In light of this, a glass-ceramic (GC) has been incorporated into chitosan and gelatin electrospun nanofibers (240-360 nm), which MEFs were loaded on it for healing acceleration. The GC was doped with silver to improve the antibacterial activity. The bioactive nanofibrous scaffolds demonstrated antibacterial and superior antibiofilm activities against Gram‐negative and Gram‐positive bacteria. The nanofibrous scaffolds were biocompatible, hemocompatible, and promoted cell attachment and proliferation. Nanofibrous skin substitutes with or without Ag‐doped GC nanoparticles did not induce an inflammatory response and attenuated LPS‐induced interleukin‐6 release by dendritic cells. The rate of biodegradation of the nanocomposite was similar to the rate of skin regeneration under in vivo conditions. Histopathological evaluation of full‐thickness excisional wounds in BALB/c mice treated with mouse embryonic fibroblasts‐loaded nanofibrous scaffolds showed enhanced angiogenesis, and collagen synthesis as well as regeneration of the sebaceous glands and hair follicles in vivo.